Implementasi Media YouTube Yufid Kidz dalam Pembelajaran Keterampilan Berbicara Bahasa Arab - Ida Fitriana; Miftakhul Jannah, Ida (Tarling : Journal of Language Education, 2024)
This research deeply examines and describes how the Yufid Kidz YouTube platform can be used as an effective learning medium to improve Arabic speaking skills, better known as maharatul kalam. As a basic skill that must be mastered after listening skills (maharatul istima'), speaking skills can be honed through various methods such as direct conversation, discussion, and other interactive activities. This research is a type of descriptive qualitative research, with data sources coming from secondary data such as articles, books, and relevant scientific journals. The data collection technique used in this research is library research, where the data obtained is analyzed qualitatively with an inductive approach. The results showed that YouTube Yufid Kidz is an alternative learning media that has great potential to improve students' Arabic speaking skills. The use of this platform can enrich existing learning methods and provide a more enjoyable and effective learning experience for students. The platform presents images and explanations that are simple, interesting, easily understood by students, and supports visual-audio-based learning with multi-media principles so that Arabic language learning becomes more interactive and contextual.